2016
DOI: 10.1111/aen.12222
|View full text |Cite
|
Sign up to set email alerts
|

Feeding and parasitism of adultStenoperlaspp. (Plecoptera: Eustheniidae) in New Zealand

Abstract: The adult diets of two species of stonefly, Stenoperla prasina (Newman, 1845) and Stenoperla maclellani Zwick, 1979 were investigated by gut content analysis. Adults were collected throughout New Zealand by light-trapping at 77 streamside sites most of which were located in native forest. S. prasina was widely distributed and collected at 43 sites, whereas S. maclellani was sampled at 10 sites in the South Island only. Of 200 S. prasina and 42 S. maclellani dissected, 36% and 69% respectively, contained food.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…While no intermediate hosts of New Zealand hairworms have been experimentally confirmed, Winterbourn (2005) found that adult stoneflies of the species Spaniocerca zelandica and Cristaperla fimbria exhibit a high prevalence of infection (69-90%) by nematomorph larvae. Winterbourn and Pohe (2016) subsequently found nematomorph larvae in two species of another New Zealand stonefly genus, Stenoperla. Previous studies of stonefly dispersal have demonstrated that adult stoneflies can travel hundreds or even thousands of metres along and between stream corridors (Briers et al 2004;MacNeale et al 2005).…”
Section: Lack Of Host-parasite Co-structurementioning
confidence: 99%
“…While no intermediate hosts of New Zealand hairworms have been experimentally confirmed, Winterbourn (2005) found that adult stoneflies of the species Spaniocerca zelandica and Cristaperla fimbria exhibit a high prevalence of infection (69-90%) by nematomorph larvae. Winterbourn and Pohe (2016) subsequently found nematomorph larvae in two species of another New Zealand stonefly genus, Stenoperla. Previous studies of stonefly dispersal have demonstrated that adult stoneflies can travel hundreds or even thousands of metres along and between stream corridors (Briers et al 2004;MacNeale et al 2005).…”
Section: Lack Of Host-parasite Co-structurementioning
confidence: 99%
“…Hynes 1942;Brinck 1949;Harper & Hynes 1972). Among other studies in captivity, that of Collier and Scarsbrook (2000) is highly significant, since they reported that when Zelandoperla decorata is fed sugar solution and fungi, the females develop eggs, and both males and females gain weight (in Winterbourn & Pohe 2017). Smith and Collier (2000), in their study on Gripopterygidae, found some incongruences between results obtained by means of gut content analyses and those from stable isotope analyses (coming from both the animals and the potential food resources), indicating that a combined investigation of the diet and the movements during the adult life is needed to resolve these issues.…”
Section: Feeding Habits Of Antarctoperlariamentioning
confidence: 98%
“…This also occurs in some Antarctoperlaria. For instance, Stenoperla species (Eustheniidae) from New Zealand mature a large quantity of eggs during their last nymphal stage, but they actively feed when adults (Winterbourn & Pohe 2017). Obviously, this does not mean that adult feeding in most stoneflies does not play an important role in the adult stage for egg maturation and/or other biological aspects, as demonstrated by some authors (e.g.…”
Section: Adult Feedingmentioning
confidence: 99%
See 2 more Smart Citations